The association of depression with child abuse among Indonesian adolescents - Dhamayanti, Meita; Noviandhari, Anindita; Masdiani, Nina; Pandia, Veranita; Sekarwana, Nanan (BMC pediatrics, 2020)
Background Depression is one of the most prevalent mental health problems among adolescents. Mental health problems might be the result of child abuse considering that their prevalences are increasing simultaneously in Indonesia. The aim of this study was to determine the association between depression and a history of abuse among adolescents. Methods An analytic cross-sectional study was conducted on 786 junior high school students from Bandung City, West Java, Indonesia. Subjects were selected using two-stage cluster sampling. The Children’s Depression Inventory (CDI) and the ISPCAN Child Abuse Screening Tool (ICAST) questionnaires were applied to assess depression and a history of abuse, respectively. Depression was diagnosed by a psychiatrist after a positive score on the CDI. The data were analysed using chi-square tests and multiple regression. Results A history of child abuse was associated with depression in adolescents. All dimensions of child abuse had a significant association with depression. Psychological violence had the highest risk factor for the occurrence of depression (PR = 6.51), followed by exposure to violence and physical violence. Sexual violence was not a common dimension of child abuse among students. Psychological violence had the strongest association with depression, and victims were three times more likely to develop depression (POR = 3.302, p = 0.004). Conclusion Psychological violence was proven to be a strong risk factor for developing depression symptoms among adolescent students. While each victimization domain remained a significant predictor of depression, the experience of multiple domains during a child’s life-course may predict mental health risk. Early detection and interventions to prevent abuse and its consequences are critical.